Injectable and thermally contractible hydroxypropyl methyl cellulose/Fe3O4 for magnetic hyperthermia ablation of tumors. (June 2017) - Wang, Fengjuan; Yang, Yang; Ling, Yi; Liu, Jianxin; Cai, Xiaojun; Zhou, Xiaohan; Tang, Xiuzhen; Liang, Bing; Chen, Yini; Chen, Hangrong; Chen, Dengming; Li, Chunhong; et al.
Abstract: The development of efficient strategies for the magnetic hyperthermia ablation of tumors remains challenging. To overcome the significant safety limitations, we developed a thermally contractible, injectable and biodegradable material for the minimally invasive and highly efficient magnetic hyperthermia ablation of tumors. This material was composed of hydroxypropyl methyl cellulose (HPMC), polyvinyl alcohol (PVA) and Fe3 O4 . The thermal contractibility of HPMC/Fe3 O4 was designed to avoid damaging the surrounding normal tissue upon heating, which was confirmed by visual inspection, ultrasound imaging and computed tomography (CT). The efficient injectability of HPMC/Fe3 O4 was proven using a very small needle. The biosafety of HPMC/Fe3 O4 was evaluated by MTT and biochemical assays as well as flow cytometry (FCM). All the aforementioned data demonstrated the safety of HPMC/Fe3 O4 . The results of in vitro and ex vivo experiments showed that the temperature and necrotic volume of excised bovine liver were positively correlated with the HPMC/Fe3 O4 weight, iron content and heating duration. The in vivo experimental results showed that the tumors could be completely ablated using 0.06 ml of HPMC/60%Fe3 O4 after 180 s of induction heating. We believe that this novel, safe and biodegradable material will promote the rapid bench-to-bed translation of magnetic hyperthermia technology, and it is also expected to bring a new concept for the biomaterial research field.